KMO-driven metabolic reconfiguration and its impact on immune cell infiltration in nasopharyngeal carcinoma: a new avenue for immunotherapy - Nijun Chen; Yuan Zong; Chen Yang; Lei Li; Yang Yi; Jiawen Zhao; Xiaoyu Zhao; Xianfei Xie; Xingmei Sun; Ning Li; Liting Jiang (Cancer Immunology, Immunotherapy)
Abstract Background Nasopharyngeal carcinoma (NPC), a malignant epithelial tumor, is characterized by a complex tumor microenvironment (TME) and closely associated with metabolic dysfunction. Mitochondrial metabolism plays a crucial role in supporting the rapid proliferation of tumor cells. However, the specific response of mitochondria to the NPC microenvironment and their role in regulating the metabolic heterogeneity of the tumor remain poorly understood. Methods Tissue samples and corresponding clinicopathological data were collected from 72 primary NPC patients and 36 non-tumor controls. Histological analysis, coupled with public transcriptomic database interrogation, was utilized to investigate mitochondrial dynamics and metabolism across different cell types. Characterizing the interactions within the tumor-immune microenvironment (TME), we identified mitochondrial genes associated with prognosis in NPC. Additionally, we explored the relationship between key mitochondrial genes, the TME, and the response to immunotherapy. Results Malignant epithelial cells in NPC exhibited altered mitochondrial metabolism, including dysregulation of amino acid and glucose metabolism, when compared to non-malignant cells. The mitochondrial-related hub gene KMO was significantly downregulated in NPC tissues relative to normal controls. Low expression of KMO was associated with poorer survival outcomes in patients. Furthermore, KMO expression was negatively correlated with DNA repair mechanisms and hypoxia. In addition, KMO levels were inversely associated with the upregulation of both oxidative phosphorylation (OXPHOS) and glycolysis pathways within the NPC tumor microenvironment (TME). Single-cell transcriptomic analysis revealed that KMO was primarily expressed in B cells, with some contribution from myeloid cells. Importantly, KMO levels positively correlated with the infiltration of various immune cell populations, including B cells, T cells, and macrophages, as well as inflammatory signatures. Further investigation indicated that individuals with elevated KMO expression may exhibit heightened sensitivity to immune checkpoint blockade (ICB) therapy compared to those with lower KMO expression. Conclusion The mitochondrial hub gene KMO plays a pivotal role in regulating mitochondrial metabolism and modulating the immune microenvironment in NPC. As a potential prognostic biomarker, KMO may offer valuable predictive insights, and targeting KMO could represent a promising therapeutic strategy for NPC, potentially enhancing the efficacy of immunotherapies.